2020
DOI: 10.1021/acsami.0c07577
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study of the Growth Mechanism and Photoelectrochemical Activity of a BiVO4/Bi2S3 Nanowire Composite

Abstract: A BiVO4/Bi2S3 composite comprising Bi2S3 nanowires on top of a BiVO4 film was prepared via hydrothermal reaction. Because additional Bi3+ ions were not delivered during the reaction, BiVO4 served as the Bi3+ ion source for the development of Bi2S3. A detailed growth mechanism of the nanowire was elucidated by an analysis of the concentration gradient of Bi3+ and S2– ions during the reaction. The in situ growth was followed by the etching of BiVO4 to Bi3+ and VO4 3– ions and regrowth to Bi2S3, which resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…is about $1.8 and $2.9 times higher than that of v-Bi 2 S 3 (3.8 mA cm À2 ) and i-Bi 2 S 3 (2.4 mA cm À2 ), which is the highest one for Bi 2 S 3 based electrode up to date. [43][44][45][46][47] In addition, the onset potential of v-Bi nanoparticle catalyst on the electrode surface decreases the kinetic barrier for charge transfer across the electrode-electrolyte interface, providing a more efficient transfer of holes in the PEC water oxidation. 7 The incident photon-to-current conversion efficiency (IPCE) of the v-Bi 2 S 3 /Co 3 O 4 at 1.23 V vs. RHE is $85%, at 420 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…is about $1.8 and $2.9 times higher than that of v-Bi 2 S 3 (3.8 mA cm À2 ) and i-Bi 2 S 3 (2.4 mA cm À2 ), which is the highest one for Bi 2 S 3 based electrode up to date. [43][44][45][46][47] In addition, the onset potential of v-Bi nanoparticle catalyst on the electrode surface decreases the kinetic barrier for charge transfer across the electrode-electrolyte interface, providing a more efficient transfer of holes in the PEC water oxidation. 7 The incident photon-to-current conversion efficiency (IPCE) of the v-Bi 2 S 3 /Co 3 O 4 at 1.23 V vs. RHE is $85%, at 420 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that v-Bi 2 S 3 /Co 3 O 4 produced the highest photocurrent density in Na 2 SO 4 (J H 2 O ) electrolyte among the three samples, indicating the best PEC performance of v-Bi 2 S 3 /Co 3 O 4 . At 1.23 vs. RHE under the simulated AM 1.5G illumination, the J H 2 O of v-Bi 2 S 3 /Co 3 O 4 (7.0 mA cm À2) is about $1.8 and $2.9 times higher than that of v-Bi 2 S 3 (3.8 mA cm À2 ) and i-Bi 2 S 3 (2.4 mA cm À2 ), which is the highest one for Bi 2 S 3 based electrode up to date [43][44][45][46][47]. In addition, the onset potential of v-Bi 2 S 3 /Co 3 O 4 is negatively shied in Na 2 SO 4 electrolyte, demonstrating the introduction of Co 3 O 4…”
mentioning
confidence: 99%
“…As displayed in Fig. 4 a, two separated peaks in the Bi 4f XPS spectrum at 158.3 and 163.6 eV are 4f 7/2 and 4f 5/2 hybridized orbitals of the Bi 4f orbital energy level for BC-5 sample, respectively [ 33 ]. Compared with bare Bi 2 S 3 NSs, the peak position shifts to the high binding energy, indicating that the electron density on the Bi 2 S 3 surface in BC-5 nanocomposites is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Hong et al have extensively studied the photoelectrochemical action with a BiVO 4 /Bi 2 S 3 composite that revealed a band gap of 1.35 eV, which is more favorable for photovoltaic conversion. 5 In the recent past, transition-metal sulfides of Bi 2 S 3 have attracted interest in sensing applications due to their low cost, nontoxicity, biocompatibility, and sensing ability. 6 One-dimensional (1D) materials such as nanoribbons, nanotubes, nanowires, and nanorods based on Bi 2 S 3 and their catalytic ability have attracted more attention in recent decades for electrochemical sensor applications.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth sulfide (Bi 2 S 3 ) is related to the metal chalcogenide group, particularly A 2 V B 3 VI (A = As, Sb, and Bi; B = S, Se, and Te), and has attracted wide attention as a potential electrode material in different fields with a direct band gap of E g = 1.3–1.7 eV. The semiconducting material of Bi 2 S 3 is a very active electron transport agent in photoelectrochemical activity. Hong et al have extensively studied the photoelectrochemical action with a BiVO 4 /Bi 2 S 3 composite that revealed a band gap of 1.35 eV, which is more favorable for photovoltaic conversion . In the recent past, transition-metal sulfides of Bi 2 S 3 have attracted interest in sensing applications due to their low cost, nontoxicity, biocompatibility, and sensing ability .…”
Section: Introductionmentioning
confidence: 99%